High intensity in interspinous ligaments: a diagnostic sign of lumbar instability and back pain for degenerative lumbar spondylolisthesis - Jiang Jiang; Min Chen; Ding-an Huang; Jun-Jie Luo; Jian-bang Han; Ming Hu; Ying-feng Wang (BMC Musculoskeletal Disorders)
Abstract Background To investigate the clinical significance of high intensity signals in interspinous ligaments at the affected segment in degenerative lumbar spondylolisthesis (DLS), as well as to determine the most effective diagnostic modalities for evaluating segmental instability. Methods This study reviewed a consecutive series of patients with L4/5 DLS between July 2023 and December 2023. The enrolled patients were divided into two groups based on the presence or absence of high-intensity signals in interspinous ligaments: the higher group (Group H), and the non-higher group (Group NH). Translational and angular motion was determined using flexion and extension (FE) radiographs or a sitting lumbar lateral radiograph with a supine sagittal MR image (combined, S-MR). The five-repetition sit-to-stand test (5R-STS) was employed to evaluate patients’ objective functional impairment (OFI). Results Overall, 73 patients were enrolled in this study, and there were 22 (30.1%) patients in group H and 51(69.9%) patients in group NH, with an average age of 60.3 ± 8.1 years. The patients in Group H exhibited significantly longer 5R-STS times and serious OFI compared to those in Group NH. Compared to Group NH, Group H exhibited significantly higher SP in the sitting position (21.8% vs 16.7%; P < 0.001*), while no significant differences were observed in the upright, flexion, extension, and supine MRI positions (all P values > 0.05). In Group H, “instability” was recognized in 77.3% of patients using S-MR versus 40.9% patients using FE (P < 0.001); While in Group NH, no significant difference was observed in the incidence of “instability” between FE and s-MR (37.3% vs. 31.4%, P = 0.53). Overall, a significantly higher incidence of instability was found in Group H compared to Group NH (77.3% vs .37.3%, P < 0 .001*). Conclusions DLS with a high intensity within the interspinous ligaments is a distinct subgroup associated with segmental instability, the combination of 5R-STS and S-MR should be regarded as the most clinically relevant approach for assessing OFI and lumbar instability.